“Curiouser and curiouser!” Russian Translations of Alice’s Adventures in Wonderland From a Literary Polysystem Perspective - Kuvshinova, Anna (My University, 2014)
This research analyses five widespread Russian translations of Alice’s Adventures in Wonderland by Lewis Carroll which became available to the Russian reader in the 1970s and 1980s from a polysystem theory perspective. Polysystem theory claims that translated texts adjust to the target literary polysystem and adopt a specific position within it. In order to reveal and understand how the target literary polysystem influences the translation, the original and the translations have been compared and contrasted with each other. Textual, descriptive and comparative analyses show that the translators’ interpretations and literary customs of the target culture condition the translation of specific phenomena and influence the form and the content of the translated text. Hence, if treated as a children’s book, Alice tends to be adapted to the Russian culture and to be given the features typical of the target children’s literature. However, if considered as an adult book, Alice retains its foreignness even though the translator alters the text regarding the needs of the implied reader. Nevertheless, the translation produced inevitably differs from the original due to the fact that texts exist in different cultural and literary systems. Thus the role of the translator is emphasised, because the translators, who share the values and beliefs of the target cultural system, impact on the readers’ perception of the text and the characters.
Keywords: literary translation; children’s literature; polysystem theory; fi=Englannin kieli|en=English language|; fi=Master's Degree Programme in Intercultural Studies in Communication and Administration|